Reference and information services : an introduction - Smith, Linda C.; Wong, Melissa Autumn (Santa Barbara Libraries Unlimited, 2016)
"Thoroughly updated, this go-to work links you--and though you, your patrons--to the significant changes that have occurred in reference and information sciences thanks to the growth in digital content"--
Includes bibliographical references and index.
Keywords: Reference services (Libraries); Information services; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / Cataloging & Classification; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / Collection Development